Kinetostatic Modeling and Performance Analysis of Redundant-Actuated 4-PSS&S Compliant Parallel 3-DOF Micro-Rotation Mechanism - Jun Ren; Ruihan Xiao; Yahao Lu (Micromachines)
This paper presents a novel redundant-actuated 4-PSS&S compliant parallel micro-rotation mechanism (P represents the actuated prismatic joint and S denotes the spherical pair) with three rotational degrees of freedom. First, compliance models of the flexure spherical hinge, each branch and the whole mechanism are established using the compliance matrix method. Then, the mechanism is simplified as an equivalent spring system to establish two kinetostatic models, with their correctness validated through finite element simulations. Finally, a comparative analysis is conducted on the performance of the 3-PSS&S mechanism, non-redundant-actuated 4-PSS&S mechanism and redundant-actuated 4-PSS&S mechanism. The results show the following: ① For the 4-PSS&S mechanism, redundant actuation with optimized actuating force distribution effectively reduces the peak actuating force by up to 50% (average 40.95%), achieving an average 10.79% reduction compared to the 3-PSS&S mechanism. ② The 4-PSS&S mechanism’s output stiffness increases by 26.68% in the θx and θy directions and by 33.31% in the θz direction compared to the 3-PSS&S mechanism. ③ Optimal force distribution significantly reduces the parasitic axis drift of the redundant-actuated 4-PSS&S mechanism at the constrained flexure spherical hinge S3, indicating higher motion accuracy. ④ The workspace volume of the redundant-actuated 4-PSS&S mechanism expands by 94.32% compared to the 3-PSS&S mechanism and by 372.89% compared to the non-redundant-actuated 4-PSS&S mechanism.